Structural, Morphological and Dielectric Properties of Ru- and Eu-Co-Doped Strontium Apatite Nanoparticles - Gurgenc, Turan; Macit, Cevher Kursat; Biryan, Fatih; Gurgenc, Ezgi; Ozel, Cihan; Bellucci, Stefano (Asia Pacific Acad Science Pte. Ltd., 2023)
Background: Bone is a dielectric material. Thus, improving the dielectric properties of bioceramics has become an important issue in recent years. In this study, we aimed to investigate the effects of europium (Eu) and ruthenium (Ru) doping on the structural, morphological, and dielectric properties of strontium apatites (SrAp). For this, pure, Eu- and Ru-doped SrAp nanoparticles were synthesized by the hydrothermal method. Methods: Hydrothermal synthesis was carried out at 200 degrees C for 3 h. The structural and morphological properties of the synthesized SrAp nanoparticles were investigated by field emission scanning electron microscopy (FE-SEM), X-ray diffraction (XRD), and energy-dispersive X-ray spectroscopy (EDX) analyses. The dielectric properties of the synthesized nanoparticles were investigated. Results: Eu and Ru additives reduced the XRD peak intensities and broadened the peaks. The characteristic XRD peaks of SrAp were affected by Eu and Ru doping. Doping of Ru and Eu co-doped with Ru shifted the planes below the 2 theta values. The synthesized particles are in the nanoscale range and in the form of nanorods. The lengths of the nanorods were shortened and expanded by the addition of Eu and Ru. The closest value to 1.67, which is the stoichiometric ratio of Sr/P, was obtained for the sample that had Eu and Ru co-doped (1.47). The Eu and Ru addition affected the electrical properties of the synthesized nanoparticles. Superior dielectric constants, dielectric losses, and alternative current (AC) conductivities were obtained compared with those for Eu- and Ru-doped pure SrAp samples. Conclusions: The results showed that the dielectric properties of SrAp nanoparticles improved; thus, more studies should be performed. The nanoparticles produced in this study can likely be used as biomaterials in biosensors, biomedical applications, and orthopedic and dental applications.
Keywords: hydrothermal method; strontium apatite; europium; ruthenium; biomaterial; dielectric